Contact Surface Resistivity as a Favorable Condition of Commutation Process - Chemerys, V.T. (Электронное моделирование, 2017)
It is shown on the basis of analysis for electrotechnical model of commutation process in the contact zone of rail accelerator of macrobodies that surface resistivity of electrodes of a contact pair is a necessary condition for favorable commutation of current in electromechanical transducers with a sliding contact. In the model of accelerator which has the increasing resistivity of the rail surface layer along with the rise of armature motion velocity it is shown that the volume Joule’s losses in the skin layer per unit of rail length can be constant in spite of its resistivity growth, so causing no additional superheating of the conductor. A discussion is performed concerning similar situation in the rotating commutator machines. На основе анализа электротехнической модели коммутационного процесса в контактной зоне рельсового ускорителя макротел показано, что резистивный характер поверхности электродов контактной пары является необходимым условием, способствующим коммутационному процессу в электромеханических преобразователях со скользящим контактом. Для модели ускорителя, имеющей возрастающее удельное сопротивление поверхностного слоя рельсов по мере возрастания скорости движения якоря, показано, что объемные джоулевы потери на единицу длины скин-слоя рельсов могут оставаться неизменными, не вызывая дополнительного перегрева проводника в скин-слое в связи с увеличением его удельного сопротивления. Подобная ситуация рассмотрена для электрических машин вращательного движения. На основі аналізу електротехнічної моделі комутаційного процесу в контактній зоні рейкового прискорювача макротіл показано, що резистивний характер поверхні електродів контактної пари є необхідною умовою сприяння комутаційному процесу в електромеханічних перетворювачах з ковзаючим контактом. Для моделі прискорювача, що має зростаючий питомий опір поверхневого шару рейок в міру збільшення швидкості руху якоря, з’ясовано, що об’ємні втрати енергії на джоулеве тепло в розрахунку на одиницю довжини скінового шару рейок можуть залишатися незмінними, не викликаючи додаткового перегрівання провідника у скіновому шарі через зростання його питомого опору. Розглянуто роль резистивного характеру матеріалу електродів контактної пари в електричних машинах обертального руху.